Model Indigenous Penguatan Kelembagaan Adat Suku Sakai Kabupaten Bengkalis - Abdul Mirad; Eka Eka; Aguswan Aguswan (JOELS: Journal of Election and Leadership, 2021)
Indigenous model of strengthening traditional institutions of the Sakai tribe in Bengkalis Regency. This research aims to formulate a model that is suitable for strengthening and developing the institutions of the Sakai tribe. The research method uses a qualitative approach, namely describing the role of indigenous peoples in strengthening the social institutions of the Sakai tribe in Bengkalis Regency. The results of the research achieved formulate a policy model for strengthening customary institutions based on regulations, normative and culture that can provide input on the formulation, implementation and evaluation of the role of indigenous peoples in strengthening traditional institutions of the Sakai tribe as a symbol of the Bengkalis district culture.